Prenatal Sunshine Exposure and Birth Outcomes in China - Xin Zhang; Yixuan Wang; Xi Chen; Xun Zhang (Institute of Labor Economics (IZA), 2019)
This paper is one of the first to examine the associations between prenatal sunshine exposure and birth outcomes, specifically the incidence of low birth weight (LBW) and small for gestational age (SGA), based on a nationally representative birth record dataset in China. During the sample period in the 1990s, migration was limited in rural China, allowing us to address the identification challenges, like residential sorting and avoidance behaviors. We found a nonlinear relationship between the length of sunlight and birth outcomes. In particular, prenatal exposure to increasing sunshine was associated with a reduction in the incidence of LBW and SGA, especially in the second trimester during pregnancy. This finding was consistent with the clinical evidence suggesting positive effects of sunshine on birth outcomes via obtaining vitamin D or relieving maternal stress.
Keywords: I12; J13; I18; Q51; 330; small for gestational age; low birth weight; sunshine duration; China